2006
DOI: 10.1167/iovs.05-1635
|View full text |Cite
|
Sign up to set email alerts
|

No Pathogenic Mutations Identified in theCOL8A1andCOL8A2Genes in Familial Fuchs Corneal Dystrophy

Abstract: The Arg434His mutation in the COL8A2 gene, previously associated with FECD, has been shown not to segregate with the disease phenotype, and thus may not be considered a disease-causing mutation. The absence of pathogenic mutations identified in the COL8A1 or COL8A2 genes in affected members of 15 pedigrees with familial FECD indicates that other genetic factors are involved in the development of this autosomal dominant corneal dystrophy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 10 publications
0
18
1
Order By: Relevance
“…12 Moreover, a patient with the R155Q and T502M mutations showed no corneal guttae or endothelial cell decrease. Although Aldave et al (2006) 15 identified the R434H mutation of the COL8A2 gene in American FECD patients, R434H was also detected in an individual with keratoconus.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…12 Moreover, a patient with the R155Q and T502M mutations showed no corneal guttae or endothelial cell decrease. Although Aldave et al (2006) 15 identified the R434H mutation of the COL8A2 gene in American FECD patients, R434H was also detected in an individual with keratoconus.…”
Section: Discussionmentioning
confidence: 93%
“…6,8,13,14 Also, in English FECD patients, three missense mutations of the COL8A2 gene, R155Q, R304Q, and R434H, were identified in familial and unrelated forms of common FECD, 8 whereas Aldave et al (2006) and Kobayashi et al (2004) reported that no COL8A2 variants associated with the common FECD subtype, late-onset FECD have been identified. 15 Furthermore, an observed association between the COL8A2 gene variants and FECD, as well as other corneal diseases, including keratoconus and posterior polymorphous corneal dystrophy (PPCD), was reported by others. 6,8,12,15 Therefore, it is important to identify the genetic factors that determine susceptibility to FECD to gain an insight into the pathogenesis of FECD in Korean patients, because the susceptibility of mutations in COL8A2 can vary in different ethnicities and in the age of onset.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…Candidate genes selected for screening have included genes involved in other forms of endothelial dystrophy. Although the COL8A2 gene was implicated in a fraction of patients with late-onset disease (Biswas et al 2001), this has been contradicted by subsequent studies in which the sequence changes reported to be pathogenic for late-onset FECD were found in the normal population; in addition, there was no evidence for association of COL8A2 mutations with late-onset FECD in a series of families screened in two different studies (Kobayashi et al 2004;Aldave et al 2006). A small fraction of patients (4/89) with late-onset FECD were found to have heterozygous mutations in the SLC4A11 gene, which is responsible for CHED2 (AR-CHED; see following section); none of these mutations occurred in the control population, and corresponding mutant proteins were shown to be defective in localization and turnover in relation to the wild type (Vithana et al 2006).…”
Section: Genetics Of Fecdmentioning
confidence: 97%